Ludloff's open reduction of the hip: long-term results - Sosna, A; Rejholec, M (Journal of pediatric orthopedics, 1992)
Long-term results of Ludloff's open reduction of the hip were studied in 62 joints of 56 children with an average follow-up of 11 years (range 5-18 years). Results were considered good in 76% and poor in 24%. A decisive factor in assessing long-term results was a proper centric reduction of the femoral head. The most frequent obstacles to proper reduction were a shortened inferomedial part of a joint capsule with the transverse ligament pulled into the joint cavity (14%), joint capsule contracture (100%), and an inverted limbus (92%), which was accompanied in 17% of patients by an impression of reflected head of the rectus femoris. Earlier nonoperative treatment affected the success of the reduction as well as long-term results.
Keywords: následné studie; ortopedie; Hip Dislocation, Congenital; mužské pohlaví; ženské pohlaví; Infant; vývojová kyčelní dysplazie; Humans; Female; Orthopedics; kojenec; Follow-Up Studies; lidé; Male